William Marion Jardine papers - Jardine, William Marion, 1879-1955.
Correspondence, speeches, lectures, articles, notes, and scrapbooks of clippings documenting Jardine's service as U.S. secretary of agriculture and U.S. minister to Egypt and to his tenure as president of Wichita University, 1934-1949. Pertains chiefly to the economic aspects of agriculture and rural life. Correspondents include Milton Stover Eisenhower, Herbert Hoover, Alfred M. Landon, Andrew W. Mellon, Henry L. Stimson, and Harry Hines Woodring.
Educator, public official, and diplomat.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Eisenhower, Milton Stover, -- 1899-1985 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; Landon, Alfred M. -- 1887-1987 -- Correspondence; Mellon, Andrew W. -- 1855-1937 -- Correspondence; Stimson, Henry L. -- 1867-1950 -- Correspondence; Woodring, Harry Hines, -- 1887-1967 -- Correspondence; United States. -- Department of Agriculture; University of Wichita; Agriculture -- Economic aspects; Diplomatic and consular service, American -- Egypt; Rural conditions; Egypt -- Foreign relations -- United States; United States -- Foreign relations -- Egypt; Cabinet officers; Diplomats; Educators; Public officials